The Role of Marketing and Business Approach on SME Development - Bajrami, Hykmete; Fejza, Vjosa (Ekonomika, 2020)
Almost two decades after the war, Kosovo is an import-based consumption economy. Its weak export does not get any closer to imports, and this makes the country dependent on foreign assistance and remittances. The structure of the economy, with trade as a dominating undertaking, a sustenance-based agricultur,e and very limited production facilities, is a very fragile ground for economic development. Incentives to attract FDI were not competitive with neighboring countries and the country development is still lagging behind. In this respect, the lack of a proper marketing and business approach is present too. Theory and practice from developed countries show that firms that want to increase sales produce what is needed or/and wanted from costumers. In most of the market economy countries, when one wants to engage in business, the first step to start is market research; this rarely happens in Kosovo, people go in business almost ad hoc. Evidence shows that firms do neglect marketing by being mainly sales-oriented; they do produce what they think is good for the costumers and then use lots of resources to convince them that this is what they need. In general, this paper analyses the dynamics of economic development in Kosovo in post-conflict time, the government efforts to change the economic structure, its constraints with emphasis on perception of marketing and the role of consumers for SMEs in the country. In particular, the paper tries to explain why companies need to change their way of doing business; hence, it recommends the change of their business approach. The research, done with 200 small and medium enterprises (SMEs) in Kosovo, shows there are rather few firms that understand marketing and through it fight competition and strive to establish long-term relationships with their customers.